2018
DOI: 10.1002/ece3.4020
|View full text |Cite
|
Sign up to set email alerts
|

High CO2 decreases the long‐term resilience of the free‐living coralline algae Phymatolithon lusitanicum

Abstract: Mäerl/rhodolith beds are protected habitats that may be affected by ocean acidification (OA), but it is still unclear how the availability of CO 2 will affect the metabolism of these organisms. Some of the inconsistencies found among OA experimental studies may be related to experimental exposure time and synergetic effects with other stressors. Here, we investigated the long‐term (up to 20 months) effects of OA on the production and calcification of the most common mäerl species of southern Portugal, Phymatol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…In a previous long‐term experiment with Phymatolithon lusitanicum (Sordo et al, ), the authors also observed no effect of high CO 2 under low irradiance (8 μmol photons m −2 s −1 ). However, when irradiance was increased during the short‐time incubations (to a maximum of 200 μmol photons m −2 s −1 ), the differences among treatments increased proportionally to CO 2 concentration.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…In a previous long‐term experiment with Phymatolithon lusitanicum (Sordo et al, ), the authors also observed no effect of high CO 2 under low irradiance (8 μmol photons m −2 s −1 ). However, when irradiance was increased during the short‐time incubations (to a maximum of 200 μmol photons m −2 s −1 ), the differences among treatments increased proportionally to CO 2 concentration.…”
Section: Discussionmentioning
confidence: 80%
“…Even if values close to 50 μmol photons m −2 s −1 were occasionally recorded on the field, most of the time these algae are exposed to low light and temperature conditions. In a previous long‐term experiment with P. lusitanicum , Sordo et al () observed a loss of pigmentation, especially accentuated at the acidified algae, but only after 20 months of high CO 2 conditions. During these experiments, algae were cultivated at low light and temperature conditions, and these conditions increased their resilience to a long‐term exposure to high CO 2 .…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations